Plano de Desenvolvimento da Escola (PDE): o processo de implantação de uma nova proposta de descentralização em duas escolas da rede municipal de ensino de Natal de 1999 a 2002 - Neves, Vilma Lúcia Silva (2003)
The 1988 Constitution was the legal marc to define changes in Brazilian State with major importance to the layout of public politician. In that moment of redefinitions e openness to new ways the redemocratization, participation and decentralization of public school had as their starter the elementary school. This work focus on the manage of FUNDESCOLA, particularly one of its politics called PDE (Educational Development Plan) wich purpose is guarantee a better quality in teaching and spread out democracy throughout its methodology. It was chosen two public schools: Professor Ulisses de Góis and Antonio Campos. The theoretical and methodological orientation is based on the theory of participative democracy developed by authors such as Putnam and Pateman. They says that a cultural background precedes individual participation in society. The collected data (educational legislation, surveys with all sectors of schools and technicians of Natal educational secretary, and relevant documents of de institutions) showed that PDE. Implementation had opposite runnings in the schools studied. In one, as a consequence of bad preparations of its teachers to absorve its methodology, PDE failed. In another way, PDE achieved its goals, especially helping the structure of action plans of the school and the administrative organization making possible several pedagogic activities planned. The work concludes that the main factor the failure or success of PDE relies on the organizational (both political and pedagogical) structure of each school. This discovery implies three important guidelines when comes to formulation of public politicians: a) Constitution of school; b) the local actors who manages the actions; c) the colletive interest in taking part of decisions